The Era of Meer & Souda and Urdu Ghazal in Sindh. : (Themes & Trends) - Khalid Mahmood Rana; Dr. Tanzeem ul Firdous (Zaban-o-Adab, 2022)
The sindh in past was like a country “hind & sindh” civilization of this area was very precious in history. After invasion of Arabs, sindh suffered from different attacks of foreign invaders as well as local conspiracies. The invaders mostly spoke Arabic and Persian which affected local languages indeed, as a law of nature. Sindhi language claims the existance from ancient era but writing style was declared by British rulers in 1843 A.D . . . . Simoultaneosly Arabic and Persian affected local style of poetry –bait, waii, seh hurfee, ghazal, qaseeda and masnavi. In written history, urdu ghazal in sindh started from Mulla Abdul hakeem “Atta” Thatavi 1040A.H-1140A.H. the era of great urdu poet Meer taqi meer & mirza muhammad Rafi sauda documented a golden era of urdu poetry in subcontinent. Urdu ghazal in ghazal in sindh under review period of Meer & sauda also documented similar kind of poetry , beside Mulla abdul hakeem atta , mir hyder kamil , Meer muhammad sabir , rohal faqeer , murad faqeer zangeja , syed sabit ali shah , meer zia uddin zia , the great sofi poet sachal sarmast , muhammad yousaf nanik , qadir bakhash baidal, played a vital role in development of urdu in sindh. The trend of poetry in sindh based in spiritual preaching of love and brotherhood, protest against inhuman activities, wahdat ul wajood. We can quote the era of Meer and sauda in sindh geared comprehensive evolution role to develop a best era of Urdu ghazal in Sindh.